PENELITIAN MENYELURUH TENTANG ANALISIS KOHESI DALAM PENELITIAN LATAR BELAKANG TESIS YANG DITULIS OLEH MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS DI UNIVERSITAS NEGERI SEMARANG - Hardiana, Nabilla Dwi; Nabila Irsani Manurung; Emeliya Sukma Dara (ELT in Focus, 2024)
This research delves into the analysis of cohesion in the background of thesis research by students of the English Language Education Program at Semarang State University. Focusing on theory, literature, and descriptive qualitative methodology, the study reveals the essential role of cohesion in shaping the structure and meaning in academic writing. Findings highlight the use of various cohesion tools such as demonstrative references, substitution, ellipsis, conjunctions, lexical cohesion, and collocation, as well as their practical implications in forming a coherent narrative. Additionally, the research explores the variability of cohesion usage in various disciplines, providing important guidance for thesis writers to adjust their writing strategies according to norms in their respective fields of study. The results of this study contribute both theoretically and practically to the understanding of cohesion analysis, English language teaching, and the development of academic curricula.